A Digital Glucose Control Strategy via Subcutaneous Insulin Infusion. Issue 40 (2022) - Ferdinando, M. Di; Borri, A.; Gennaro, S. Di; Pepe, P.; Palumbo, P
Abstract: In this paper, the plasma glucose regulation problem for Type 2 diabetic patients by subcutaneous insulin infusion is studied. A nonlinear time-delay model of the glucose-insulin regulatory system, which takes into account the subcutaneous infusion of insulin, is exploited for the design of a quantized sampled-data static state feedback glucose controller. Quantization in both input/output channels is considered. Spline interpolation methodologies are used in order to obtain an approximation of suitable needed past values of the system state that cannot be always available from the buffer. The stabilization in the sample-and-hold sense is used in order to prove that the proposed digital glucose regulator ensures the semi-global practical stability of the related closed-loop tracking error system, with arbitrarily small final target ball. The proposed digital glucose regulator is validated through simulations.